China's electric vehicles adoption: implications for sustainable electricity, transportation, and net-zero emissions - Abudu, Hermas; Sai, Rockson; Hossin, Md Altab; Botah, Elvis Banoemuleng (Frontiers in Sustainable Energy Policy, 2024)
IntroductionThe rapid adoption of electric vehicles in China is a key strategy for decarbonizing the transportation sector, facilitating the transition to sustainable energy, and meeting the country's net-zero emissions goals. Notwithstanding this, limited research has explored how technological advancement influences electric vehicle adoption in the context of achieving sustainable electricity.MethodsThis study addresses this gap by integrating vehicle range, smart charging infrastructure, and battery electric vehicles into an econometric count framework utilizing countrywide data-driven insights.ResultsThe findings demonstrate that technological advancements-specifically in vehicle range and the expansion of charging infrastructure-are vital solutions in driving battery electric vehicles acceptance. These advancements are essential for revolutionizing the transportation industry and contributing to the country's emissions reduction targets.DiscussionHowever, this presents a dual challenge: balancing increased electricity demand while capitalizing on these technologies to meet net-zero goals. The study highlights critical policy implications, particularly the need to advance electric vehicle material technologies through the use of critical minerals including aluminum and lithium. By prioritizing these materials, producers can improve electric vehicles' efficiency and support the integration of renewable energy sources. The study concludes that incorporating renewable energy solutions, like solar-powered charging stations, is crucial for ensuring sustainable electricity. Policies encouraging public-private partnerships and investments in research on materials and smart charging technologies are crucial for reducing charging times and improving vehicle range. Additionally, fostering public-private collaborations to install smart charging infrastructure equipped with Internet-of-Things technology at parking slots can create a synergistic effect, significantly boosting electric vehicle adoption in China.